2013
DOI: 10.1177/1474515113477273
|View full text |Cite
|
Sign up to set email alerts
|

The CHARMS Study: cardiac patients’ experiences of sexual problems following cardiac rehabilitation

Abstract: Background: Sexual problems are common among cardiac patients. Further information is required on patients' experiences of sexuality, and preferences for, sexual counselling.Aim: To characterise sexual dysfunction and related factors among patients following cardiac rehabilitation and examine related treatment delivery.Methods: Telephone interviews with 382 patients (32% response rate) recruited from six hospital rehabilitation centres.Results: Seventy-nine percent were male; average age was 64 years (SD 9.8).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 37 publications
2
29
2
1
Order By: Relevance
“…The rates of sexual health problems vary based on a variety of related factors such as patient's age, severity of disease and co-morbidities that range between 20% [17] and 70% [18]. About half (46%) of 382 patients with CADs in six rehabilitation centers reported sexual problems [19]. In one study conducted in Jordan (N = 124), about three quarters of patients with heart diseases reported that their sexual health is being altered [20].…”
Section: The Cads and Sexual Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…The rates of sexual health problems vary based on a variety of related factors such as patient's age, severity of disease and co-morbidities that range between 20% [17] and 70% [18]. About half (46%) of 382 patients with CADs in six rehabilitation centers reported sexual problems [19]. In one study conducted in Jordan (N = 124), about three quarters of patients with heart diseases reported that their sexual health is being altered [20].…”
Section: The Cads and Sexual Healthmentioning
confidence: 99%
“…For example, patients may need to know how their sexual health is being affected by the illness, by medications and associated side effects, when can they resume their sexual activities, what are the warning signs reportable to the physician, what sex enhancing medications can they use and what preparations are available to aid in resuming sexual activities. Byrne and colleagues reported that about half of 382 cardiac patients preferred the opportunity of addressing their sexual health concerns by health care providers [19].…”
Section: Patients' Needs For Sexual Health Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Health-related quality of life is substantially undermined owing to reduced strength and capacity for physical activity, compromised sleep, and emotional components ( Figure 1). Additional factors associated with erosion of health-related quality of life in advanced heart failure include sleep-disordered breathing (including, but not limited to, obstructive sleep apnea), which may also be detrimental to prognosis [4], depression (which has been associated with, but not causally linked to, marked increases in mortality) [5,6], anxiety [5], and extensive reporting of sexual dysfunction and dissatisfaction [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Patients are often reluctant to seek medical advice regarding ED, necessitating proactive enquiry. The Cardiac Health and Relationship Management and Sexuality study (CHARMS) assessed cardiac rehabilitation patients; ED was associated with increased anxiety and depression, with 12% classing the deterioration of sexual lives following diagnosis/coronary event a serious problem 33. The multifactorial causes of ED require recognition to allow incorporation into rehabilitation programmes.…”
Section: Recommended Evaluation Of Sexual Dysfunction For Cardiologistsmentioning
confidence: 99%